A method for preparing a high reflectivity composite metal electrode

CN114843387BActive Publication Date: 2026-10-13LASER RES INST OF SHANDONG ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210437172.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-25
Publication Date
2026-10-13
Estimated Expiration
2042-04-25

AI Technical Summary

Technical Problem

但是目前高反射率电极,多采用图形电极技术,工艺复杂,成本高

Benefits of technology

1.本发明涉及到的制备高反射率复合电极的方法,不需要利用光刻技术制备图形电极结构,简化了工艺步骤,可以降低生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 220425113232
    Figure 220425113232
  • Figure 220425113235
    Figure 220425113235
Patent Text Reader

Abstract

The application provides a high-reflection composite metal electrode preparation method, which comprises the following preparation steps: step 1) providing a GaAs-based photoelectric device epitaxial wafer, wherein the structure of the GaAs-based photoelectric device epitaxial wafer comprises, from bottom to top, a GaAs substrate, a buffer layer, an n-GaAs ohmic contact layer, an active layer, a p-GaAs, and a p-GaP ohmic contact layer; step 2) cleaning the GaAs-based photoelectric device epitaxial wafer; step 3) evaporating a first electrode layer on the p-GaP ohmic contact layer of the cleaned GaAs-based photoelectric device by using an electron beam evaporation coating technology, and the sequence of the electrode film layers is Zn / Au; step 4) rapidly heat annealing the Zn / Au electrode; and step 5) evaporating a second electrode layer on the annealed Zn / Au electrode, and the sequence of the electrode film layers is Ti / Au.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor light-emitting devices, and more specifically to a method for preparing a high-reflectivity composite metal electrode. Background Technology

[0002] As a semiconductor light-emitting device, the luminous efficiency of LEDs has always been a research hotspot and a crucial factor affecting their performance. Currently, the light extraction efficiency of LEDs is relatively low, resulting in most of the light energy being absorbed by the materials and converted into heat energy, which seriously affects the luminous performance of LEDs and limits the development of high-power LEDs.

[0003] Currently, most high-power gallium arsenide (GaAs)-based LEDs employ a flip-chip vertical structure, consisting of, from bottom to top: substrate, p-electrode, p-GaP, p-GaAs, active region, n-GaAs, and n-electrode. Traditional p-type electrodes typically use Zn / Au or Ti / Au structures. These two electrode structures offer good stability and low contact resistivity. However, a significant portion of the light emitted from the active region within the chip is absorbed by the electrode and substrate, reducing the LED's luminous efficiency. High-reflectivity electrodes can effectively solve the light absorption problem between the electrode and substrate, eliminating the need for a DBR structure, simplifying the process, and reducing costs. However, current high-reflectivity electrodes often employ patterned electrode technology, which is complex and costly. Summary of the Invention

[0004] To overcome the shortcomings of existing technologies, this invention provides a method for preparing high-reflectivity composite metal electrodes. This method is simple, low-cost, and can achieve the preparation of p-GaP electrodes with high reflectivity, low contact resistivity, and high stability, thereby improving LED luminous efficiency.

[0005] This invention is achieved through the following technical solution: a method for preparing a high-reflectivity composite metal electrode, comprising the following preparation steps: Step 1) Provide a GaAs-based optoelectronic device epitaxial wafer, the structure of which, from bottom to top, includes a GaAs substrate, a buffer layer, an n-GaAs ohmic contact layer, an active layer, a p-GaAs layer, and a p-GaP ohmic contact layer. Step 2) Clean the epitaxial wafer of the GaAs-based optoelectronic device; Step 3) The first electrode layer is deposited on the p-GaP ohmic contact layer of the cleaned GaAs-based optoelectronic device using electron beam evaporation deposition technology. The order of the electrode film layers is Zn / Au. Step 4) Perform rapid thermal annealing on the Zn / Au electrode; Step 5) Deposit a second electrode layer on the annealed Zn / Au electrode again, with the order of the electrode films being Ti / Au.

[0006] Preferably, the epitaxial wafer cleaning step includes: ultrasonic cleaning with trichloroethylene, acetone, and ethanol sequentially for 5 minutes, rinsing with deionized water for 5 minutes, and drying with nitrogen. The purpose of cleaning is to remove particles, organic and inorganic impurities from the surface of the epitaxial wafer to avoid affecting the contact rate and reducing electrode adhesion and reliability.

[0007] Preferably, the electrode deposition employs electron beam evaporation coating technology, and the cavity temperature during the deposition process does not exceed 40°C. If the temperature exceeds 40°C, it will affect the surface smoothness and adhesion of the deposited electrode.

[0008] Preferably, the thickness of the Zn layer in the first electrode is 4~6 nm, and the thickness of the Au layer is 30~40 nm.

[0009] Preferably, the rapid thermal annealing process involves an annealing temperature of 400~420℃ and an annealing time of 60~70s.

[0010] If the annealing temperature is too low or the annealing time is too short, Au and Ga cannot react to form AuGa, resulting in a low acceptor concentration and a low hole concentration near the contact surface, thus failing to reduce resistivity. If the temperature is too high or the annealing time is too long, some harmful Au-Ga reaction complexes will be formed, which is also detrimental to reducing resistivity. Furthermore, if the temperature is too high, Au will aggregate and easily clump, which is not conducive to the formation of high reflectivity in the electrode.

[0011] Preferably, the thickness of the Zn layer in the first electrode is 4~6 nm, and the thickness of the Au layer is 30~40 nm, preferably 30 nm.

[0012] Preferably, the second electrode has a Ti layer with a thickness of 20-25 nm and an Au layer with a thickness of 500-600 nm.

[0013] The thickness of the first electrode Au layer is 30~40 nm, and the thickness of the second electrode Au layer is 500~600 nm. The thickness of the first electrode Au layer has a significant impact on the contact resistivity and reflectivity. The thickness of the second Au layer is based on the overall electrode thickness. The overall electrode thickness is generally greater than 500 nm to meet the requirements of electrode lead and other device processing.

[0014] This invention utilizes electron beam evaporation to deposit electrodes. The deposition sequence is as follows: first, a first electrode, Zn / Au, is deposited; then, the first electrode undergoes rapid thermal annealing; finally, a second electrode, Ti / Au, is deposited. The rapid thermal annealing of the first electrode ensures good ohmic contact between the GaP and Zn / Au electrodes, reducing contact resistivity. The second electrode is a crucial layer for enhancing light reflectivity. By not annealing the second electrode, the influence of the annealing process on its reflectivity is avoided, resulting in a smooth and bright second electrode layer with higher reflectivity.

[0015] The highly reflective Au metal layer of the second electrode reflects the light transmitted to the electrode back into the chip, where it is then emitted again, thus improving the LED's light extraction efficiency. The Ti metal layer enhances the adhesion between the first and second electrodes, preventing electrode detachment. Compared to traditional electrodes prepared by rapid thermal annealing after a single deposition process, this method of staged deposition with rapid thermal annealing only of the first electrode achieves the fabrication of electrodes with high reflectivity and low contact resistivity.

[0016] Beneficial technical effects of the present invention: 1. The method for preparing high-reflectivity composite electrodes disclosed in this invention does not require the use of photolithography to prepare patterned electrode structures, thus simplifying the process steps and reducing production costs.

[0017] 2. The present invention employs a Zn / Au / Ti / Au electrode structure and a two-step vapor deposition and selective thermal annealing method, which can effectively improve the electrode reflectivity and form excellent ohmic contact.

[0018] 3. The method provided by this invention has a wide range of applications. It is not only applicable to the preparation of GaAs-based LED devices, but also applicable to the preparation of other GaAs-based optoelectronic devices, including solar cells, photodetectors, etc. Attached Figure Description

[0019] Figure 1 This is a cross-sectional schematic diagram of the LED epitaxial structure according to a preferred embodiment of the present invention; Figure 2 This is a cross-sectional schematic diagram of the electrode structure according to a preferred embodiment of the present invention.

[0020] Among them: 1. GaAs substrate, 2. Buffer layer, 3. n-GaAs ohmic contact layer, 4. Active layer, 5. p-GaAs, 6. p-GaP ohmic contact layer, 7. Zn layer, 8. First Au layer, 9. Ti layer, 10. Second Au layer, 11. First electrode layer, 12. Second electrode layer. Detailed Implementation

[0021] The present invention will be further described in detail below with reference to specific embodiments, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention. The scope of protection of the present invention includes, but is not limited to, the following embodiments. Any modifications made to the details and form of the technical solution of the present invention without departing from the spirit and scope of this application shall fall within the scope of protection of the present invention.

[0022] Example 1 A method for preparing a high-reflectivity composite metal electrode includes the following preparation steps: Step 1) Provide a GaAs-based optoelectronic device epitaxial wafer. The structure of the GaAs-based optoelectronic device epitaxial wafer, from bottom to top, includes a GaAs substrate 1, a buffer layer 2, an n-GaAs ohmic contact layer 3, an active layer 4, a p-GaAs 5, and a p-GaP ohmic contact layer 6. See [link to relevant documentation]. Figure 1 .

[0023] Step 2) Clean the epitaxial wafer of the GaAs-based optoelectronic device; the epitaxial wafer cleaning steps include: ultrasonic cleaning with trichloroethylene, acetone and ethanol for 5 min in sequence, rinsing with deionized water for 5 min, and drying with nitrogen. Step 3) The first electrode layer 11 is deposited on the p-GaP ohmic contact layer 6 of the cleaned GaAs-based optoelectronic device using electron beam evaporation deposition technology. The order of the electrode layers is Zn / Au. The thickness of the Zn layer 7 is 4 nm, and the thickness of the first Au layer 8 is 30 nm. Step 4) Perform rapid thermal annealing on the Zn / Au electrode; the annealing temperature is 420℃ and the annealing time is 60s; Step 5) The second electrode layer 12 is deposited again on the annealed Zn / Au electrode. The order of the electrode layers is Ti / Au. The thickness of the Ti layer 9 is 20 nm and the thickness of the second Au layer 10 is 600 nm.

[0024] Figure 2 This is a cross-sectional schematic diagram of the electrode structure of a GaAs-based LED device according to an embodiment of the present invention, as shown below. Figure 2 As shown, the second electrode layer 12 includes, from bottom to top, a Ti layer 9 and a second Au layer 10.

[0025] The first electrode layer 11, composed of Zn layer 7 and first Au layer 8, forms an excellent ohmic contact with the p-GaP ohmic contact layer after rapid thermal annealing at 420℃ for 60s. This effectively improves the carrier injection efficiency and is beneficial to the improvement of LED photoelectric efficiency.

[0026] The second electrode layer 12, composed of Ti layer 9 and second Au layer 10, is not subjected to rapid thermal annealing, resulting in a smooth and flat surface with high optical reflectivity. Specifically, Ti layer 9 improves the adhesion of the first electrode layer 11 and the second electrode layer 12, enhancing electrode stability; the second Au layer 10 reflects light incident on the second electrode layer 12 into the active layer 4 of the LED device, improving the luminous efficiency of the LED device.

[0027] The p-GaP electrode, which is composed of the first electrode layer 11 and the second electrode layer 12, has low contact resistivity and high optical reflectivity, which can significantly improve the luminous efficiency of LED devices.

[0028] Example 2 A method for preparing a high-reflectivity composite metal electrode includes the following preparation steps: Step 1) Provide a GaAs-based optoelectronic device epitaxial wafer. The structure of the GaAs-based optoelectronic device epitaxial wafer, from bottom to top, includes a GaAs substrate 1, a buffer layer 2, an n-GaAs ohmic contact layer 3, an active layer 4, a p-GaAs 5, and a p-GaP ohmic contact layer 6. See [link to relevant documentation]. Figure 1 .

[0029] Step 2) Clean the epitaxial wafer of the GaAs-based optoelectronic device; the epitaxial wafer cleaning steps include: ultrasonic cleaning with trichloroethylene, acetone and ethanol for 5 min in sequence, rinsing with deionized water for 5 min, and drying with nitrogen. Step 3) The first electrode layer 11 is deposited on the p-GaP ohmic contact layer 6 of the cleaned GaAs-based optoelectronic device using electron beam evaporation deposition technology. The order of the electrode layers is Zn / Au. The thickness of the Zn layer 7 is 6 nm and the thickness of the first Au layer 8 is 30 nm. Step 4) Perform rapid thermal annealing on the Zn / Au electrode; the annealing temperature is 400℃ and the annealing time is 70s; Step 5) The second electrode layer 12 is deposited again on the annealed Zn / Au electrode. The order of the electrode layers is Ti / Au. The thickness of the Ti layer 9 is 25 nm and the thickness of the second Au layer 10 is 500 nm.

[0030] Comparative Example 1 The thickness of the first electrode Au layer in Comparative Example 1 is 10 nm, and the rest is the same as in Example 1.

[0031] Comparative Example 2 The thickness of the first electrode Au layer in Comparative Example 2 is 20 nm, and the rest is the same as in Example 1.

[0032] Comparative Example 3 The thickness of the first electrode Au layer in Comparative Example 3 is 40 nm, and the rest is the same as in Example 1.

[0033] Comparative Example 4 The thickness of the first electrode Au layer in Comparative Example 4 is 50 nm, and the rest is the same as in Example 1.

[0034] The reflectance of Example 1 and Comparative Examples 1-4 was measured, and the results showed that the thickness of the Au metal layer of the first electrode has a significant impact on the reflectance. When the thickness of the Au metal layer of the first electrode is 10 nm, 20 nm, 30 nm, 40 nm, and 50 nm, the reflectance at a wavelength of 630 nm is 85.6%, 90.4%, 94.5%, 93.7%, and 85.3%, respectively. This is because if the Au metal layer of the first electrode is too thin or too thick, the surface roughness will increase after annealing, resulting in a decrease in reflectance.

[0035] Furthermore, when the Au metal layer of the first electrode is less than or equal to 20 nm, the contact resistivity decreases to 4.14 × 10⁻⁶. −6 Ω cm 2 This is because the Au metal layer involved in the annealing is too thin to provide enough Ga vacancies through the GaP layer, and the acceptor concentration is low, resulting in increased contact resistance.

[0036] When the thickness of the Au metal layer on the first electrode is greater than 30 nm, the contact resistance decreases and remains at 4.04 × 10⁻⁶. −6 Ω cm 2 This is because sufficient Ga vacancies are generated in the GaP layer, which reduces the contact resistance.

[0037] Therefore, based on the above summary, the preferred thickness of the Au metal layer for the first electrode is 30 nm.

[0038] Comparative Example 5 In Comparative Example 5, the first and second electrodes were all vapor-deposited and then uniformly annealed, and the remaining steps were the same as in Example 1.

[0039] By comparing Example 1 and Comparative Example 5, it was found that the electrode contact resistivity of Example 1 was the lowest at 4.04 × 10⁻⁶. −6 Ωcm 2 The reflectivity at a wavelength of 630 nm can reach a maximum of 94.5%. In contrast, after annealing, Comparative Example 5 shows a minimum electrode contact resistivity of 4.11 × 10⁻⁶. −6 Ωcm 2However, the reflectivity decreased, reaching 82.3% at a wavelength of 630 nm. Both the electrodes of Example 1 and Comparative Example 5, after annealing, exhibited low contact resistivity. This is because, after annealing, Au and Ga react at a certain temperature to form AuGa, generating a certain amount of Ga in the GaP surface space. Then, Zn atoms diffuse into GaP, occupying the original Ga positions, increasing the hole concentration near the contact surface, increasing the tunneling probability, and thus further reducing the resistivity. However, Example 1 showed a significantly higher reflectivity than Comparative Example 5. This is because, during the high-temperature alloying process, due to the material properties of Au, Au tends to aggregate and easily agglomerate, which is detrimental to the formation of high reflectivity in the Au / Zn electrode.

Claims

1. A method for preparing a high-reflectivity composite metal electrode, characterized in that: The following preparation steps are included: Step 1) Provide a GaAs-based optoelectronic device epitaxial wafer, the structure of which from bottom to top includes a GaAs substrate (1), a buffer layer (2), an n-GaAs ohmic contact layer (3), an active layer (4), a p-GaAs (5), and a p-GaP ohmic contact layer (6). Step 2) Clean the epitaxial wafer of the GaAs-based optoelectronic device; the cleaning steps of the epitaxial wafer of the GaAs-based optoelectronic device include: ultrasonic cleaning with trichloroethylene, acetone and ethanol in sequence for 5 min, rinsing with deionized water spray for 5 min, and drying with nitrogen gas. Step 3) Deposit the first electrode layer (11) on the p-GaP ohmic contact layer (6) of the cleaned GaAs-based optoelectronic device; the first electrode layer (11) in step 3) is Zn / Au; the thickness of the Zn layer (7) is 4-6nm and the thickness of the first Au layer (8) is 30-40nm. Step 4) Perform rapid thermal annealing on the first electrode layer (11) Zn / Au electrode; the annealing temperature is 420℃ and the annealing time is 60s; Step 5) Deposit a second electrode layer (12) on the annealed Zn / Au electrode again; The order of the second electrode layers (12) in step 5) is Ti / Au, the thickness of the Ti layer (9) is 20-25nm, and the thickness of the second Au layer (10) is 500-600nm.

2. The method for preparing a high-reflectivity composite metal electrode according to claim 1, characterized in that: The electrode deposition in steps 3) and 5) employs electron beam evaporation coating technology, and the cavity temperature during the deposition process does not exceed 40°C.

Citation Information

Patent Citations

  • Red light emitting diode with high-reflectivity metal reflecting layer and preparation method thereof

    CN103811626A